2018
DOI: 10.1111/oik.05452
|View full text |Cite
|
Sign up to set email alerts
|

The role of flow velocity combined with habitat complexity as a top–down regulator in seagrass meadows

Abstract: Large‐scale losses of seagrass areas have been associated with eutrophication events, which have led to an overproduction of photosynthetic organisms including epiphytes. Grazers that feed on epiphytes can exert a significant top–down control in the system, but the effects of physical factors on grazing activity and feeding behaviour have been rarely examined. We addressed the combination of hydrodynamic regime and seagrass shoot density can alter the feeding and foraging behaviours of mesograzers. A full fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 105 publications
1
16
0
Order By: Relevance
“…(2018), studying molluscan assemblages associated with the macroalga Asparagopsis armata in the Iberian Peninsula, raised the hypothesis that local differences found were due to environmental variables, and Tanaka & Leite (2003) have discussed the importance of the association of habitat complexity and physical conditions in the variations of gammarid assemblages living in Sargassum habitats at small spatial scales, while Jiménez-Ramos et al . (2019) have experimentally demonstrated the importance of habitat structure and abiotic factors such as hydrodynamics, on the structuring of macrophyte ecosystems. Thus, the influence of environmental factors, in association with habitat complexity, may explain the differences found herein and should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…(2018), studying molluscan assemblages associated with the macroalga Asparagopsis armata in the Iberian Peninsula, raised the hypothesis that local differences found were due to environmental variables, and Tanaka & Leite (2003) have discussed the importance of the association of habitat complexity and physical conditions in the variations of gammarid assemblages living in Sargassum habitats at small spatial scales, while Jiménez-Ramos et al . (2019) have experimentally demonstrated the importance of habitat structure and abiotic factors such as hydrodynamics, on the structuring of macrophyte ecosystems. Thus, the influence of environmental factors, in association with habitat complexity, may explain the differences found herein and should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even though changes in seagrass traits could be seen as positive for individual seagrass plants (i.e., increasing growth or photosynthetic rate), it could also lead to changes in their functions and imbalances in their biotic and abiotic interactions, negatively affecting the ecosystem services they perform. For example, it could lead to changes in hydrodynamic conditions or sedimentation rates (Fonseca et al, 2019) which affect the distribution of organisms within the canopies, and therefore, biodiversity (González-Ortiz et al, 2014;Jiménez et al, 2019;Meysick et al, 2019). Seagrass responses to changes in nutrient and temperature conditions can be measured by changes in their trait values which are often used as indicators of environmental stress in coastal management.…”
Section: Introductionmentioning
confidence: 99%
“…In Caño de Cortadura, the size effect analysis revealed differential herbivory rates by mesograzers between transplanted and local leaves, with the local ones being found more palatable (i.e., higher leaf nitrogen content and lower leaf carbon and fiber content and thickness) and therefore supporting higher rates of herbivory. In summary, the influence of environmental factors and meadow characteristics (e.g., density, size) on seagrass herbivory is not only determined by its effects on leaf palatability, but also by its influence on consumer feeding, even may have consequences in their swimming behavior, as recently was described by Jiménez‐Ramos et al (2019) in a flume study.…”
Section: Discussionmentioning
confidence: 68%
“…Seagrass canopies create refuges for small invertebrates against predation, thus increasing recruitment and growth of invertebrates (Connolly 1995). Moreover, Jiménez‐Ramos et al (2019) demonstrated that this habitat complexity created by seagrass meadows (i.e., shoot density) affected mesograzer feeding, with higher feeding rates being recorded at higher shoot densities under low and moderate hydrodynamic flows. In our study, higher herbivory rates in C. nodosa meadows were found in populations with high shoot density and areas exposed to milder hydrodynamic conditions (i.e., Caño de Cortadura and Santibáñez), which is in agreement with this previous study (Jiménez‐Ramos et al 2019).…”
Section: Discussionmentioning
confidence: 99%